Analisis Perbandingan Mesh Wi-Fi dan Konvensional untuk Jaringan Kampus di Lebak - Cancan Firman Wilantika; Yulikuspartono Yulikuspartono (Jurnal Teknologi Terpadu, 2026)
The demand for reliable internet connectivity on campus has increased as digital learning systems have been implemented. Conventional Wi-Fi networks often face limitations in coverage, connection stability, and service quality when the number of users increases. This study aims to compare the performance of Mesh Wi-Fi and Conventional Wi-Fi in improving campus network service quality. The methods include a literature review, infrastructure survey, Mesh Wi-Fi installation, and Quality of Service (QoS) measurements, including throughput, latency, packet loss, and signal coverage. Data were collected through direct testing in three buildings during peak and off-peak hours, as well as through a user satisfaction survey. The results show that Mesh Wi-Fi outperforms Conventional Wi-Fi, with relatively stable download and upload throughput above 90 Mbps, lower average latency (±11–13 ms), jitter below 5 ms, and packet loss of less than 1%. In contrast, Conventional Wi-Fi experiences bandwidth degradation of up to approximately 30% at the farthest building, along with increased latency and packet loss. User survey results also indicate higher satisfaction with Mesh Wi-Fi, particularly in terms of connection stability, speed, and roaming convenience.